Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am trying to prove the following for a very, very long time: $$ 2k=\sum_{j=1}^k \binom{2k+1}{2j}2^{2j}B_{2j} $$ Here, $B_{2j}$ are Bernoulli numbers.

I would be extremely happy if somebody could help me with this!

share|cite|improve this question
The following MSE link points to a computation that can easily be adapted to prove the result being asked for here. – Marko Riedel Aug 6 '14 at 2:23
up vote 6 down vote accepted

Let $B_n(X) := \sum_{i=0}^n \binom{n}{i}B_i X^{n-i}$ denote the $n$-th Bernoulli polynomial. It satisfies the symmetry relation $B_n(1-X) = (-1)^n B_n(X)$ which implies $B_n(1/2) = 0$ for odd numbers $n$. Hence $$0 = 2^{2k+1} B_{2k+1}(1/2) = \sum_{i=0}^{2k+1} \binom{2k+1}{i} B_i 2^i = 1 + (2k+1)2B_1 + \sum_{i=2}^{2k+1} \binom{2k+1}{i} B_i 2^i.$$ All summands with odd $i$ vanish since the odd-numbered Bernoulli numbers are zero, the only exception being $B_1 = -1/2$. It follows that $$0 = -2k + \sum_{j=1}^k \binom{2k+1}{2j}B_{2j}2^{2j}$$ which proves your proposition.

share|cite|improve this answer
:Thank you very much! – Daoyi Peng Apr 24 '12 at 9:43

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.